Tools to apply to financial statements to identify errors, omissions and fraud in business valuations - Tom Clevenger; Gary Baker (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
Often economists are asked to value businesses. Many times the information provided is minimal and of questionable value. Data may be provided by parties wishing to bias the valuation. The financial statements typically provided are balance sheets and income statements. These sources can be fraught with errors, omissions and even fraud. The cash flow statements derived from these statements can be misleading and any analysis from these spurious statements is sure to be questioned. A set of tools exists that can use to establish the reliability of these financial statements. Reliability is usually taken for granted in basic accounting and finance and reality is often not as assumed. The tool kit uses basic accounting and mathematical logic. This logic, teamed with basic accounting definitions and conventions, allows the economist some comfort that the statements provided for use in the business valuation are free of obvious misinformation. These tools can also help uncover some less detectable fraud. For the analysis to proceed there must be two balance sheets and the intervening income statement. By applying the accounting conventions and definitions, real, probable and possible solutions are developed and explained. After examining the relationship between the financial statements one is better able to value the business and be confident of the analysis.
Keywords: 650